ANALOGUE AND DIGITAL MINDSETS: SOME IMPLICATIONS FOR INTERCULTURAL COMMUNICATION BETWEEN WESTERN AND EASTERN ORGANISATIONS - Hiroko Noma,; Joanna Crossman, (Asian Academy of Management Journal, 2012)
Globalising forces have given rise to new relationships between organisations operating in Eastern and Western cultural contexts. Despite the rich opportunities presented by globalisation, the literature indicates that managers are challenged by the complexity of intercultural communication. This scholarly paper discusses some implications of analogue and digital mindsets for the managers of organisations in which effective inter-cultural communication across Eastern and Western contexts is crucial. We do so by adopting a multidisciplinary approach to the phenomenon and suggesting how managers may capitalise on knowledge related to analogue and digital mindsets to foster creative and holistic approaches to communication.